The Art in Science of MicroTAS 2018. Issue 12 (15th May 2019) - Cooksey, Gregory A.
Abstract : Nam-Trung Nguyen from Griffith University, Australia, was the winner of the 2018 MicroTAS Art in Science competition. He received the award certificate from Simon Neil from Lab on a Chip and Greg Cooksey from NIST.